2021
DOI: 10.52711/0974-360x.2021.00669
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostical and Phytochemical Evaluation of Aconitum heterophyllum Root

Abstract: The present work aims to study the pharmacognostical and phytochemical characteristics of the roots of Aconitum heterophyllum. The study deals with the macroscopy, microscopy, powder analysis, physicochemical standardization, and preliminary phytochemical screening of Aconitum heterophyllum roots. Anatomical studies of the tuberous roots of Aconitum heterophyllum showed distinct endodermis, a wide zone of secondary phloem, and a ring of 4 to 9 vascular strands. The powder analysis revealed the presence of sube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The species also showed thicker layers of the endodermis and pericycle (St anescu et al, 2009). Compounds containing lignin and starch grains have been described in the root of A. heterophyllum (Mathew et al, 2021), which were also reported in the present study, as previously mentioned.…”
Section: Rootsupporting
confidence: 91%
See 4 more Smart Citations
“…The species also showed thicker layers of the endodermis and pericycle (St anescu et al, 2009). Compounds containing lignin and starch grains have been described in the root of A. heterophyllum (Mathew et al, 2021), which were also reported in the present study, as previously mentioned.…”
Section: Rootsupporting
confidence: 91%
“…The arrangement of the vascular system differs between the species A. degenii , A. heterophyllum and Aconitum heterophylloides (Brühl) Stapf (syn. of Aconitum laciniatum (Brühl) Stapf (Jamtsho et al, 2022; Mathew et al, 2021; Stănescu et al, 2009), as seen in Table 1. The species also showed thicker layers of the endodermis and pericycle (Stănescu et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations